Vacuum ultraviolet spectroscopy of the lowest-lying electronic state in subcritical and supercritical water - Timothy W. Marin (Nature Portfolio, 2017)
The link between hydrogen bonding and the optical properties of water has been debated for many years, but not fully understood. Here, the authors report vacuum ultraviolet absorption spectra for subcritical and supercritical water, providing insight into the electronic structure of water and its relation to hydrogen bonding.